2019
DOI: 10.1002/jlb.2ri0919-302r
|View full text |Cite
|
Sign up to set email alerts
|

Decoding communication patterns of the innate immune system by quantitative proteomics

Abstract: The innate immune system is a collective network of cell types involved in cell recruitment and activation using a robust and refined communication system. Engagement of receptor-mediated intracellular signaling initiates communication cascades by conveying information about the host cell status to surrounding cells for surveillance and protection. Comprehensive profiling of innate immune cells is challenging due to low cell numbers, high dynamic range of the cellular proteome, low abundance of secreted protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 109 publications
(111 reference statements)
0
19
0
Order By: Relevance
“…Macrophages are found ubiquitously throughout the body and are often an early responder to bacterial infection. The interaction between macrophages and K. pneumoniae present a well-studied system to explore the relationship between host and pathogen under in vitro settings [43][44][45][46]. Macrophage cytotoxicity assays showed that deletion of chaB (leading to reduced capsule size) impacts bacterial virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are found ubiquitously throughout the body and are often an early responder to bacterial infection. The interaction between macrophages and K. pneumoniae present a well-studied system to explore the relationship between host and pathogen under in vitro settings [43][44][45][46]. Macrophage cytotoxicity assays showed that deletion of chaB (leading to reduced capsule size) impacts bacterial virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Fundamental proteomic research has unearthed a wealth of knowledge pertaining to disease pathways, identification of disease markers, and drug targets for the remediation of these studied diseases [4]. Proteomic studies of the human innate immune system have also become increasingly important to understanding the complex signaling patterns involved in responding to diseases [5]. For example, MS-based phosphoproteomics has identified signaling pathways and specific proteins that are involved in the maturation of primary T-cells [6,7] and the function of cytotoxic T-lymphocytes [8].…”
Section: Introductionmentioning
confidence: 99%
“…The information obtained from quantitative proteomic profiling can inform treatment strategies, patient stratification, molecular mechanisms underpinning phenotypic observations and details pertaining to signaling networks, and protein-protein interactions critical to the evaluated criteria (Mann, Kulak, Nagaraj, & Cox, 2013). In addition, proteomic profiling can provide valuable insight into the interplay between host and pathogen during infection and generate large datasets outlining changes from these dual perspectives in a single experiment (Ball, Bermas, Carruthers-Lay, & Geddes-McAlister, 2019;Jean Beltran, Federspiel, Sheng, & Cristea, 2017;Sukumaran et al, 2019). For example, proteomic profiling of the ocular surface during infection with Pseudomonas aeruginosa, a Gramnegative bacterial pathogen and the primary causative agent of ocular keratitis, defines global and site-specific host responses to infection and uncovers potential biomarkers for prognostic and diagnostic purposes (Yeung, Gadjeva, & Geddes-McAlister, 2020).…”
Section: Introductionmentioning
confidence: 99%